Preliminary observations of Zooplankton in Pulau Tinggi, Marine Park, Johor, Malaysia - Shuaib, Nasir; Mohammad, Maryati; Matias-Peralta, Hazel Monica; Rusiman, Mohd Saifullah; Sanusi, Shuaibu Babaji (Science Publishing Corporation, 2018)
Zooplankton was studied in Pulau Tinggi, Marine Park, Johor, Malaysia for their abundance and species diversity. Water samples were collected within three months, April, June and October 2015.Ten sampling stations were established during the study period. A total of 54 species of copepods from 29 genera and 22 families were identified. An average of 86.70 % copepods and 15.84% non-copepods were recorded among the zooplankton groups. The water quality parameters such as depth, dissolved oxygen, pH, temperature, turbidity, and salinity were measured in situ. The present study was taken to observe the abundance and diversity of zooplankton in Pulau Tinggi, Johor. This research will be helpful for fisheries authorities and marine controlling departments. The effect of different physico-chemical parameters on the biomass and density of zooplankton will be discussed in the coming paper.